Optical and electrical properties of SeO2 and NiO nanoparticles boosted the polymeric blend of PVDF and PVP for optoelectronic applications - M. A. Morsi; Nuha Y. Elamin; Lila A. Alkhtaby; Ali A. Alhazime; E. M. Abdelrazek; E. Salim; A. Rajeh (Scientific Reports)
Abstract This study investigates the impact of various weight percentages of selenium oxide/nickel oxide (SeO2/NiO) hybrid nanoparticles (NPs) on the physicochemical characteristics of a polymeric blend composed of polyvinylidene fluoride and polyvinyl pyrrolidone (PVDF/PVP). TEM images indicated the spherical shape for SeO2 NPs with an average size range of (30–40 nm) and the cubic and rectangular shape for NiO NPs with an average size range of (20–25 nm). XRD patterns revealed the semicrystalline structures in PVDF/PVP blends with SeO2/NiO NPs, with interacted nanoparticles reducing crystallinity, indicating the enhancement of chain dynamics and flexibility of the host PVDF/PVP blend. FT-IR spectra depicted the homogeneity of the host blend, through showing the main functional peaks of PVDF and PVP, and the significant activity of the added nano-fillers towards the PVDF/PVP chains through making polymer-nanoparticle interactions. The prepared nanocomposite films showed good absorption, their indirect optical band gaps were reduced, and the refractive index was enhanced after SeO2/NiO loading. The dielectric measurements revealed a significant increase due to polarized nanoparticles, resulting in polarizability under electric field conditions. The equivalent circuit model was introduced in terms of the electrical impedance spectra. The highest DC conductivity was recorded for DFPV3 of 0.75 wt% SeO2/NiO approaching 6.76 × 10−4 S/cm. The boost of DC conductivity is ascribed to the mobility of SeO2/NiO nanoparticles, signifying a linear increase in conductivity concerning field frequency. This leads to lower bulk resistance and increased bulk capacitance values, indicating the formation of more conductive channels in nanocomposite films. These experimental findings of this work have important significance for the field of optoelectronic and energy storage devices.